Phosphate-Functionalized CeO2 Nanosheets for Efficient Catalytic Oxidation of Dichloromethane - Dai, Qiguang; Zhang, Zhiyong; Yan, Jiaorong; Wu, Jinyan; Johnson, Grayson; Sun, Wei; Wang, Xingyi; Zhang, Sen; Zhan, Wangcheng (Environmental science & technology, 2018)
Tuning the nature and profile of acidic and basic sites on the surface of redox-active metal oxide nanostructures is a promising approach to constructing efficient catalysts for the oxidative removal of chlorinated volatile organic compounds (CVOCs). Herein, using dichloromethane (DCM) oxidation as a model reaction, we report that phosphate (PO x ) Brønsted acid sites can be incorporated onto a CeO2 nanosheet (NS) surface via an organophosphate-mediated route, which can effectively enhance the CeO2’s catalytic performance by promoting the removal of chlorine poisoning species. From the systematic study of the correlation between PO x composition, surface structure (acid and basic sites), and catalytic properties, we find that the incorporated Brønsted acid sites can also function to decrease the amount of medium-strong basic sites (O2–), reducing the formation of chlorinated organic byproduct monochloromethane (MCM) and leading to the desirable product, HCl. At the optimized P/Ce ratio (0.2), the PO x –CeO2 NSs can perform a stable DCM conversion of 65–70% for over 10 h at 250 °C and over 95% conversion at 300 °C, superior to both pristine and other phosphate-modified CeO2 NSs. Our work clearly identifies the critical role of acid and basic sites over functionalized CeO2 for efficient catalytic CVOCs oxidation, guiding future advanced catalyst design for environmental remediation.